Socialization of “Fill My Plate” to Elementary School Children in Liukang Loe Island, Bulukumba Regency - Syarfaini, Syarfaini; Rini, Rini Jusriani; Mallapiang, Fatmawaty; Azriful, Azriful; Fitrah, Fitrah (Sociality: Journal of Public Health Service, 2024)
Eating habits in school children are formed from an early age and form the basis of children’s nutritional intake patterns at a later age. The aim of this service is to increase school children’s knowledge about balanced nutrition and children’s skills in choosing balanced nutritious food through the socialization of “fill my plate” (in Indonesia: “isi piringku”). The target participants of this service activity are 50 elementary school children on Liukang Loe Island, Bulukumba Regency. The knowledge of the target group was assessed through pre and post-tests distributed before and after socialization. Pre-test and post test data were then analyzed using the Wilcoxon test. The results of data analysis showed that in the initial condition, the target group with sufficient knowledge of 44% increased to 68% in the condition after socialization. The Wilcoxon test results showed that there was a significant difference in knowledge level between before and after the target group received the "fill of my plate" socialization (p=0.004 <0.05). The target group of elementary school children was very enthusiastic in participating in the socialization and became a good alternative in increasing students’ knowledge related to portion intake and food variations.